Individualized Experience With Percutaneous Transcatheter Closure of Multiple Atrial Septal Defects: A Single-Center Study - Wang, Zhenquan; Zhan, Yi; Jin, Jiahui; Wu, Tingting; Zhang, Songyue; Qiu, Huixian; Wang, Qiaoyu; Wu, Rongzhou (Frontiers in Cardiovascular Medicine, 2021)
Multiple atrial septal defects (ASDs) is one type of secundum atrial septal defect, most of which have an atrial septal aneurysm or long inter-defects distance. In our retrospective single-center study, we reviewed different closure strategies for multiple ASDs. We analyzed 50 patients who underwent percutaneous transcatheter closure from May 2011 to July 2019. Information on the patients' characteristics, operation procedure, occluder selection, and complications was collected. According to the feature of the defects and device choice, multiple ASDs were divided into five groups. A successful operation was achieved in every patient. A total number of 50 patients were implanted with 58 devices, with 26 patients implanted with a single standard ASDO, six patients implanted with double standard ASDOs, and only one patient implanted with three standard ASDOs. There were 17 patients whose closure was made using the small-waist-big-edge ASDO. Seventy-six percent of the patients (38/50) had an immediate residual shunt. During the mean follow-up of 25.76 ± 22.53 months, the complete closure rate was 92%. Except for two patients with a transient atrioventricular block. Individualized experience with percutaneous transcatheter closure for multiple atrial septal defects was effective in a single-center study. After a mid-to long-term follow-up, the multiple ASDOs and small-waist-big-edge ASDO had no serious adverse events or complications.